Broadcasting the Bieber Republic: A Critical Analysis of "#thatPOWER". (July 2020) - Berman, Naomi; Platania-Phung, Chris
This article provides a critical analysis of "#thatPOWER"—a music video featuring will.i.am and Justin Bieber. This analysis focuses on the tensions and binary oppositions depicted in the video that pertain to social and geographic placement (e.g., "race, " gender, religion). Social science scholarship on youth and Wendy Brown's account of neoliberalism are drawn on to argue that while "#thatPOWER" emphasizes individual agency and social advancement via will.i.am's own achievements and aspirations, what is unintentionally promoted is an ironic vision of what we call the "Bieber Republic, " where agency via participatory democracy is erased. "#thatPOWER" neatly serves neoliberalism by tacitly "teaching" that social problems can be solved by individual achievement and mobility secured by inner energy and grit, backgrounded by market competition, consumerism, and technology. In this way "#thatPOWER" is complicit with what Brown calls the "stealth revolution" of neoliberalism.